Ammotere Abbaji as a Local Wisdom-Based Restorative Justice Mechanism in Resolving Silariang Customary Crimes - Azwad Rachmat Hambali; Zainuddin Zainuddin; Salle Salle; Muhammad Ikram Nur Fuady (UIN Sunan Gunung Djati, 2026)
Silariang marriage, in Bugis-Makassar customs, is considered a form of marriage that violates customary norms because it is conducted without the family's consent, especially from the woman's side. As a conflict resolution mechanism born from the local wisdom of the Bugis-Makassar community, Ammotere Abbaji serves as a tradition of apology performed by the Silariang couple to the woman's family to restore the fractured social relationship. This mechanism prioritises the restoration of Siri's honor, payment of customary fines, acknowledgement of marital status, and reintegration of the offender into the social order, emphasising reconciliation over retribution. The process is carried out through customary deliberations involving traditional leaders and the families of both parties, thereby reflecting the substantive principles of restorative justice. In the context of Indonesian positive law, Ammotere Abbaji is gaining increasingly open recognition, in line with the spirit of various regulations that accommodate the values of living law. However, this recognition demands more concrete systemic reforms, namely the establishment of special regulations that integrate customary mechanisms into the formal judicial process, the expansion of law enforcement officers' discretionary powers to transfer cases to communal forums, and the formation of certified customary mediation institutions with measurable rights protection standards. The novelty of this research lies in the first effort to scientifically construct Ammotere Abbaji as a model of restorative justice based on local wisdom, which possesses cultural legitimacy, structured procedures, and relevance in the reform of Indonesian criminal law (ius constituendum), thereby making an original contribution to the development of customary law and the criminal justice system in Indonesia.